Measuring Basic Capabilities of Adolescents Digital Literacy in Medan to Prevent Fake News Exposure - Mickhael Rajagukguk; Iskandar Zulkarnain (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
The aim of this study is to measure basic digital literacy skills for adolescents in Medan. The basic digital literacy skills include analyzing, verifying, and finding information obtained. Quantitative method is used in this study to analyzed the findings descriptively. The research design is applied in the form of an online survey. The population used in this study was a group of middle-aged adolescents (15-18 years) in Medan. Taro Yamame formula is used to determine the sample size of this study. Due to Taro Yamame formula, the sample size involved in this study was 300 respondents, with a margin of error of 5.76%. The results shows that teenagers in Medan generally have basic digital literacy skills to ward off fake news at a capable and very capable level. However, there are some records where teenagers are still not very able to implement the ability to analyze and find the information they get from online media.